A Bibliometric Analysis of the Relationship Between Oral Microbiome and Digestive System Diseases - JIANG Wenli; HUANG Tian; WANG Furui; ZHOU Guangbo; ZHENG Ya; WANG Yuping; HU Zenan (Xiehe Yixue Zazhi)
ObjectiveTo delineate the current research landscape, emerging hotspots, and frontiers regarding the relationship between the oral microbiome and digestive system diseases.MethodsWe retrieved publications from the Web of Science Core Collection database using topic-specific queries on "oral microbiome" and "digestive diseases." Bibliometric analysis was performed using VOSviewer, CiteSpace, and the "bibliometrix" package in R for data mining and visualization.ResultsA total of 1228 eligible articles were included. Analysis revealed that research on the correlation between oral microbiota and digestive system diseases will remain a global hotspot. Academic institutions dominated the publications, with centralized institutional distribution and team-based collaboration, though overall collaboration networks remained fragmented. Geographically, the United States emerged as the leading contributor, followed by China and the United Kingdom. While China-U.S. collaborations were prominent, China's engagement with other regions remained limited. Current research hotspots focus on the interplay between oral microbiota and gut microbiota, inflammatory bowel disease (IBD), and digestive system tumors.ConclusionsResearch in this field demonstrates high activity and diversity. Studies on the associations of oral microbiota with gut microbiota, IBD, and digestive system tumors (particularly esophageal, gastric, pancreatic, and colorectal cancers) remain prominent. Future studies should prioritize elucidating underlying mechanisms and innovating in biomarker discovery and application. However, insufficient collaboration and resource-sharing among institutions currently hinder progress in this field.